1975
DOI: 10.1161/01.cir.52.6.1161
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly progressive obstructive cardiomyopathy in infants with Noonan's syndrome. Report of two cases.

Abstract: SUMMARYThis 23-month-old white boy was first admitted to Jackson Memorial Hospital, Miami, Florida, at one day of age. He had been the product of a normal pregnancy and delivery, and weighed 3.97 kg at birth. At another hospital he was noted to be cyanotic and heart murmur was heard. A sibling had died of heart failure at two weeks of age. On admission the patient was noted to be cyanotic only when cry- From

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(28 citation statements)
references
References 11 publications
3
25
0
Order By: Relevance
“…2,3 HCM is the second most commonly associated cardiac abnormality and tends to affect predominantly the interventricular septum and left ventricle. [4][5][6][7][8][9] In the case presented here, bulging of the hypertrophied septum into the right ventricular outflow tract caused RVOT obstruction, which manifested itself as right-side hypertrophic obstructive cardiomyopathy. 11,12 Because the hypertrophied muscle bundles were positioned infundibulary, this case was thought to be different from double-chambered right ventricle.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…2,3 HCM is the second most commonly associated cardiac abnormality and tends to affect predominantly the interventricular septum and left ventricle. [4][5][6][7][8][9] In the case presented here, bulging of the hypertrophied septum into the right ventricular outflow tract caused RVOT obstruction, which manifested itself as right-side hypertrophic obstructive cardiomyopathy. 11,12 Because the hypertrophied muscle bundles were positioned infundibulary, this case was thought to be different from double-chambered right ventricle.…”
Section: Discussionmentioning
confidence: 68%
“…Although several cases of biventricular HCM with right-and/or leftside outflow obstruction have been reported in infants with Noonan syndrome, relatively few cases have been reported in adults. [4][5][6][7] Although no mention was made whether their patients showed the Noonan phenotype, Maron et al reported RVOT obstruction to be relatively common in infants and young children with HCM, but rare in older patients with HCM. 16 This difference between infants and adults can be explained as follows.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The clinical course of hypertrophic cardiomyopathy is variable because it may develop in later childhood and gradually increase in severity, remain stable over many years, or be rapidly progressive in infancy. 203,211 Histopathologic studies demonstrate myocyte fiber disarray resembling nonsyndromic familial hypertrophic cardiomyopathy. Treatment is similar to that in familial hypertrophic cardiomyopathy including the use of beta blockers or surgery to reduce outflow tract obstruction.…”
Section: Cardiovascular Abnormalities During Childhoodmentioning
confidence: 99%